Successful percutaneous treatment of osteoid osteoma in a 13 month-old boy with radiofrequency ablation under CT guidance - Cennet Sahin; Yunus Oc; Naim Ediz; Aylin Hasanefendioglu Bayrak (Acta Orthopaedica et Traumatologica Turcica, 2019)
We present a 13-month-old boy who had a successful Computed Tomography (CT) guided percutaneous radiofrequency ablation (RFA) treatment for the osteoid osteoma (OO) on proximal part of the tibial diaphysis.The complaints of the patient were being restless due to pain and refusing to bear any weight on his left leg for 6 months. An asymmetrical cortical thickening and a focal sclerosis was detected on medial proximal diaphysis of the left tibia on radiographs and axial T2-weighted STIR-MR image showed bone marrow and soft-tissue edema with low-signal-intensity nidus due to central calcification with a high-signal-intensified unmineralized periphery. CT findings (the nidus on the cortex of tibia with well circumscribed lucent region around a central sclerotic dot and cortical thickening around the nidus) confirmed the diagnosis of OO.After CT guided percutaneous RFA treatment, the patient had an immediate pain relief in 24 h after and could bear weight on the leg. 12 and 16 months after RFA respectively, CT images and radiographs revealed sclerotic healing of the nidus and a slow regression of the adjacent cortical thickness without any recurrence. Keywords: Osteoid osteoma, Radiofrequency ablation, Computer tomography, Pediatric, Treatment, Percutaneous, CT guidance, Efficacy, Safety